‘Voodoo maths’, asymmetric dependency and maths blame: why collaboration between school science and mathematics teachers is so rare - Wong, V; Dillon, J (Routledge, 2019)
Mathematical reasoning and tools are intrinsic to science, yet the close and dependent relationship science has to mathematics is not reflected in either school education or science education research. This paper asks what the barriers are to a mutually beneficial relationship between the two disciplines. A two-phase qualitative interview study was used to explore the relationship between school science and mathematics education through the perspectives of science and mathematics education policy-makers and of teachers in departments which are unusual in collaborating. In total there were 36 participants. Interview data were analysed using thematic analysis. Findings show that there is an asymmetry in the dependency between school science and mathematics: science is dependent on mathematics but the reverse is not true. We discuss three consequences of this asymmetric dependency: there is greater benefit for science from any collaboration; ‘maths blame’ can arise from science teacher frustration; and science educators may believe they should have some ownership of the mathematics curriculum. Asymmetry of dependency, and therefore of benefit, will make it very difficult for mathematics and science to work together in a way which is genuinely mutually beneficial.